Possible structural phase transitions on Bi2Sr2CaCu2Oy measured by anelastic spectroscopy - Gimenez, JMD; Grandini, Carlos Roberto [UNESP]; Santos, Dayse Iara dos [UNESP] (Elsevier B.V., 2005)
Anelastic spectroscopy measurements (internal friction) are sensitive tools for the study of defects in solids, in particular the mobility of interstitial oxygen. Samples of Bi2Sr2CaCu2Oy were analyzed after being submitted to two thermal treatments in vacuum, one at 973 K and another at 673 K. Anelastic spectroscopy measurements were performed using a torsion pendulum operating at around 38 Hz and at a temperature range of 88 and 700 K with heating rate of 1 K/min and vacuum better than 10(-5) Torr. Complex relaxation structures reversible with new thermal treatments were observed. These relaxation structures were attributed to O-M structural phase transitions. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Bi-based oxides; structural phase transitions; anelastic spectroscopy